Identification of new molecules extracted from Quercus suber L. cork. (Comptes rendus biologies, 2008)
Various methods of suberin extraction have been used in order to identify monomers of this complex polymer. Pre-extraction of waxes has allowed us to identify for the first time 3-friedelanol as a terpen from cork. Moreover, the wax chemical composition found here varied from previous results since cerin was not identified while friedelin and betulin were. Three fractions were obtained: a polymeric, a monomeric and a low molecular weight fraction, the last of which has never before been described. 2,6-heptanediol was found to be the main compound of this fraction. Furthermore, depolymerisation at room temperature gives the same yields as those obtained at reflux, defining an easier and cheaper methodology.